COMPARATIVE STUDY ON THE INTEGRATION OF TPACK IN TEACHING PRACTICES - Mola, Manusetus; Santosa, Made Hery; Tenda, Priska Ernestina (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2025)
This study aims to compare the levels of mastery and implementation of Technological Pedagogical Content Knowledge (TPACK) in three study programs at San Pedro University (UNISAP): English Language Education (PBI), Primary School Teacher Education (PGSD), and Physical Education, Health, and Recreation (PJKR). The background of this study is the need to strengthen the integration of technology, pedagogy, and content in digital-based higher education. The research uses a comparative quantitative approach involving 30 lecturers (10 per Study Program) selected through purposive sampling. Data were collected using a TPACK questionnaire based on seven dimensions and analyzed with descriptive statistics and one-way ANOVA to determine differences between programs. Results show that PBI lecturers have the highest TPACK scores (average 4.61), followed by PGSD (4.18) and PJKR (3.93). ANOVA tests indicate significant differences (F (2,27) = 7.932, p < 0.01). Further Tukey HSD tests reveal significant differences between PBI and PJKR (p = 0.004) and between PBI and PGSD (p = 0.026), while the difference between PGSD and PJKR is not significant (p = 0.111). These results indicate the influence of factors such as disciplinary characteristics, technological readiness, and institutional support on variations in TPACK mastery. This study recommends the development of lecturer training tailored to the needs of each study program as a strategy to enhance professional capacity in technology integration in teaching.